(3eUGOQ GdCMcGe hTDhfgG hCWhQGgGs - (3GdfLaj, Ydj Hf eMeO QVG cGTa GdZWGA, J (B1350(3g`s ((3eMeO bdj Hf ejQRG GdNhFjfjs)
(3ChdgG (B:s
(3GdMce GdTQYj HCfg GdNWGH GdTQYj GdeJYdb HCaYGd Gdecdajf(B...s
(3BNQgG (B:s
(3ddaQO hGdLeGYI hGdSYGOI dgG aj GdOGQjf adG hLg deG PcQ dgG ef GdJaGSjQ GdCNQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U (B504s
(3GdCYdGe(B: (3L(B5(3, U(B19s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs